2021
DOI: 10.3390/genes12111660
|View full text |Cite
|
Sign up to set email alerts
|

17q12 Recurrent Deletions and Duplications: Description of a Case Series with Neuropsychiatric Phenotype

Abstract: Syndromic neurodevelopmental disorders are usually investigated through genetics technologies, within which array comparative genomic hybridization (Array-CGH) is still considered the first-tier clinical diagnostic test. Among recurrent syndromic imbalances, 17q12 deletions and duplications are characterized by neurodevelopmental disorders associated with visceral developmental disorders, although expressive variability is common. Here we describe a case series of 12 patients with 17q12 chromosomal imbalances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A 2.77 Mb deletion at 1q21.1q21.2 involving 1q21.1 syndrome. Patients with this syndrome often experience delayed development, microcephaly, ASD, and intellectual disability and display incomplete penetrance and variable phenotype [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 2.77 Mb deletion at 1q21.1q21.2 involving 1q21.1 syndrome. Patients with this syndrome often experience delayed development, microcephaly, ASD, and intellectual disability and display incomplete penetrance and variable phenotype [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the five fetuses with the 17q12 microduplication syndrome included in this study showed abnormal kidney development. The protein encoded by the LHX1 gene is an important regulator of the formation of the kidney and the urogenital system, and is also related to the development of the nervous system, playing a significant role in the growth and development and structural stability of the axons innerve cells ( 17 , 35 , 36 ). In this study, a fetus with the 17q12 microduplication syndrome displayed conditions consistent with the findings of previous literature, and its ultrasound phenotype showed mild ventriculomegaly and agenesis of the corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…It varies from asymptomatic to neurodevelopmental disorders, including developmental delay, attention deficit hyperkinetic disorder, epilepsy, autism spectrum disorder, intellectual disabilities, behavioral problems (aggression and compulsion disorders), to multisystem anomalies and abnormalities. 4 7 The duplication is commonly diagnosed by chromosomal microarray (CMA) and fails to be identified by karyotyping. 6 The treatment of choice is a multidisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%